p53-associated metabolic checkpoint regulation in a tick embryo-derived cell line - Bruno Moraes; Angélica Arcanjo; Tomohiro Okagawa; Cintia Nogueira; Antonia Brumana; Juliana L. Souza; Ariana A. Vasconcelos; Fabio C.L. Almeida; Kamila Guimarães Pinto; Alessandra Filardy; Robson Q. Monteiro; Satoru Konnai; et al. (Insect Biochemistry and Molecular Biology, 2026)

Combined thermal-electrochemical analysis uncovers the dominant cracking mechanisms in Ni-rich layered cathodes - Yang Li; Liubin Ben; Mengyu Tian; Bin Liu; Yongxue Duan; Qianlong Sun; Bo Wang; Zhongzhu Liu; Aimin Guo; Luanna Parreira; Robson Monteiro; Rogerio M. Ribas; et al. (Chemical Engineering Journal, 2026)

Proteasomal-dependent endothelial P2Y6 receptor downregulation as an adaptive mechanism limiting monocyte adhesion during intestinal schistosomiasis - Nathalia F. Oliveira; Matheus M. L. V. Monteiro; Leticia D. Crepaldi; Robson Coutinho-Silva; Luiz Eduardo B. Savio; Claudia L. Martins Silva (Purinergic Signalling, 2026)
Schistosomiasis, a complex chronic intravascular parasitic disease caused by Schistosoma mansoni , triggers a multifaceted host immune response and drives endothelial cells toward a sustained proinflammatory phenotype. The dysfunctional endothelial cells are a hallmark event that contributes to intestinal and liver damage mainly due to an increased monocyte adhesion, but the elevated morbidity unveils the lack of knowledge about disease pathogenesis. Purinergic P2Y 6 receptor (P2Y 6 R) expression is induced in some inflammatory models; therefore, we hypothesized that endothelial P2Y 6 R contributes to monocyte adhesion and mesenteric inflammation in S. mansoni -infected mice. Our results show that, unlike control mice, P2Y 6 R stimulation failed to enhance monocyte adhesion to endothelial cells from infected animals. Molecular analyses using RT-qPCR and immunocytochemistry revealed significant downregulation of P2Y 6 R expression in endothelial cells from the infected group at both transcript and protein levels. Importantly, pretreatment with a proteasome inhibitor restored both P2Y 6 R expression and function, implicating proteasomal degradation as a key mechanism underlying receptor loss during infection. Elevated lipid peroxidation in endothelial cells from the infected group further supported a role for reactive oxygen species (ROS)-dependent proteasome activation and receptor degradation. Collectively, these findings suggest that infection selectively modulates P2Y 6 R signaling by promoting proteasome-dependent downregulation of P2Y 6 R in endothelial cells, which could be an adaptive mechanism to reduce mesenteric inflammation and limit host tissue damage and morbidity during chronic infection. Graphical Abstract

A morphology-disorder dual parameter to design Ni-rich layered cathode materials - Bin Liu; Liubin Ben; Mengyu Tian; Kuiyong Liu; Yang Li; Yongxue Duan; Qianlong Sun; Bo Wang; Zhongzhu Liu; Aimin Guo; Luanna Parreira; Robson Monteiro; et al. (Chemical Engineering Journal, 2026)

Assessment of the productive and biodegradative non-enzymatic performance of Pleurotus mushrooms grown on agricultural wastes of sugarcane bagasse and banana leaves - Sabrina Alves da Silva; Jhonatan Rafael Zárate-Salazar; Robson Eduardo Pereira Monteiro; Rossana Lucena de Medeiros; Háimyk Andressa Nóbrega de Souza; Bruno de Oliveira Dias; Fillipe de Oliveira Pereira (World Journal of Microbiology and Biotechnology, 2025)

Literature review on deep learning for the segmentation of seismic images - Bruno A.A. Monteiro; Gabriel L. Canguçu; Leonardo M.S. Jorge; Rafael H. Vareto; Bryan S. Oliveira; Thales H. Silva; Luiz Alberto Lima; Alexei M.C. Machado; William Robson Schwartz; Pedro O.S. Vaz-de-Melo (Earth-Science Reviews, 2024)

Angiotensin-(1–7) decreases inflammation and lung damage caused by betacoronavirus infection in mice - Erick Bryan de Sousa Lima; Antônio Felipe S. Carvalho; Isabella Zaidan; Adelson Héric A. Monteiro; Camila Cardoso; Edvaldo S. Lara; Fernanda S. Carneiro; Leonardo C. Oliveira; Filipe Resende; Felipe Rocha da Silva Santos; Luiz Pedro Souza-Costa; Ian de Meira Chaves; et al. (Inflammation Research, 2024)

Long-term disability after cerebral ischemic stroke following a Bothrops atrox snakebite in the Brazilian Amazon - Karolaine Oliveira Bentes; Robson Luis Oliveira de Amorim; Fabiane Bianca Albuquerque Barbosa; Victor Carlos Pardo Ratis da Silva; Jefferson Valente; Fernando Almeida-Val; Jacqueline de Almeida Gonçalves Sachett; Wuelton Monteiro; Marco Aurélio Sartim (Toxicon, 2024)

Influence of Tendrils and IBA on Rhizogenic Responses in Cuttings of Black Pepper Cultivars: Histological and Histochemical Aspects - Rodrigo Sobreira Alexandre; Caroline Palacio de Araujo; André Lucas Siqueira; Elisa Mitsuko Aoyama; Tamyris de Mello; Thuanny Lins Monteiro Rosa; Carlos Eduardo Valério Raymundo; Edilson Romais Schmildt; José Carlos Lopes; João Paulo Bestete de Oliveira; Robson Bonomo; Wagner Campos Otoni (Journal of Plant Growth Regulation, 2023)

Saponite-inspired Materials as Remediation Technologies for Water Treatment: an Overview - Dihêgo Henrique L. Damacena; Pollyana Trigueiro; Victor Hugo Monteiro; Luzia Maria C. Honorio; Thiago Marinho Duarte; Robson Cunha; Marcelo B. Furtini; Maria Gardennia Fonseca; Edson C da Silva-Filho; Josy A. Osajima (Environmental Processes, 2023)

Estimation of breeding values using different densities of SNP to inform kinship in broiler chickens - Mayara Salvian; Gabriel Costa Monteiro Moreira; Robson Mateus Freitas Silveira; Ândrea Plotzki Reis; Brayan Dias D'auria; Fabrício Pilonetto; Izally Carvalho Gervásio; Mônica Corrêa Ledur; Luiz Lehmann Coutinho; Matthew Lee Spangler; Gerson Barreto Mourão (Livestock Science, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

β-Lapachone enhances the antifungal activity of fluconazole against a Pdr5p-mediated resistant Saccharomyces cerevisiae strain - Daniel Clemente de Moraes; Karina Martins Cardoso; Levy Tenório Sousa Domingos; Maria do Carmo Freire Ribeiro Pinto; Robson Q. Monteiro; Antônio Ferreira-Pereira (Brazilian Journal of Microbiology, 2020)

Development of 131I-ixolaris as a theranostic agent: metastatic melanoma preclinical studies - Thiago Barboza; Tainá Gomes; Priscylla da Costa Medeiros; Isalira Peroba Ramos; Ivo Francischetti; Robson Q. Monteiro; Bianca Gutfilen; Sergio Augusto Lopes de Souza (Clinical & Experimental Metastasis, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effect of the UV-C Radiation on Shelf Life of Vacuum-Packed Refrigerated Pirarucu ( Arapaima gigas ) Fillets - Júlia de Souza Lira Santos; Eliane Teixeira Mársico; Môsar Lemos; Miguel Antônio Cinquini; Flávio Alves da Silva; Yasmin Bugini Dutra; Robson Maia Franco; Carlos Adam Conte Junior; Maria Lúcia Guerra Monteiro (Journal of Aquatic Food Product Technology, 2018)

The role of P2 receptors in controlling infections by intracellular pathogens - Robson Coutinho-Silva; Cristiane Monteiro da Cruz; Pedro M. Persechini; David M. Ojcius (Purinergic Signalling, 2007)